Phytochemical Screening, GC-MS Analysis, and Evaluation of Antioxidants, Cytotoxicity, Analgesic, and Anti-Diarrheal Activity of the Extracts of the Leaves of Syzygium reticulatum Wight Walp - Das, Ananta Kumar; Sarkar , Uma Rani; Paul, Prosenjit; Hassan, Md. Jahid; Banik, Ratry; Das, Utpaul Chandra; Alam, Md. Khairul; Islam, Md. Nazmul; Mahmud, Md. Hasan; Shermily, Noushin; Mamun, Md. Al; Tamal, Touhidur Rahman; et al. (Trends in Sciences, 2024)
Syzygium genus is extensively used in managing different diseases such as antimicrobial, anti-diarrheal, antidiabetic, analgesic, anti-inflammatory, antioxidant, and anticancer activities. The present study aims to investigate phytochemicals by screening tests and GC-MS analysis and evaluate the antioxidants, cytotoxicity, analgesic, and anti-diarrheal activity of the extracts of the leaves of Syzygium reticulatum. The leaves of the S. reticulatum were extracted with hexane and methanol by the maceration process successively, denoted as SRH and SRM. The extract’s phytochemical analyses found flavonoids, alkaloids, saponins, tannins, glycosides, and carbohydrates. The GC-MS analysis of the methanol extract identified 8 compounds. The major components were identified as Diisooctyl phthalate (96.903 %), 2-methyltetracosane (1.094 %), and others with fewer amounts. The result of the antioxidant study of the extracts as total phenolic content of SRH 8.92 ± 0.62 and SRM 340.107 ± 11.11 mg/g, respectively, total flavonoids content of SRH 7.85 ± 0.71 and SRM 105.16 ± 0.93 mg/g, IC50 values of the DPPH (2,2-diphenyl-1-picrylhydrazyl) free radical scavenging assay of SRM was 14.67 µg/mL, SRH was 41.26 µg/mL and ascorbic acid 14.08 µg/mL; the total antioxidant capacity of SRH was 21.33 ± 2.52 mg/g, whereas SRM was 353.71 ± 4.59 mg/g. The results of these studies suggest that methanol extract has a more potent antioxidant capacity than hexane extract. The methanol extract also exhibited higher toxicity (LC50 value 49.99 µg/mL) compared to hexane extract (LC50 value 370.348 µg/mL), as revealed by the Brine shrimp nauplii cytotoxic study. An analgesic study of the methanol extract found that a lower dose (250 mg/kg) has more significant analgesic activity than the higher dose and standard drug aspirin. At 90 min, the hot plate’s highest percentage of latency elongation was 110.32, while the acetic acid-induced writhing inhibition was 63.04 %. At a dose of 500 mg/kg, the methanol extract also shown good efficacy in mice suffering from castor oil and magnesium sulfate-induced diarrhea. The findings from the study of the leaves of the S. reticulatum exhibited that methanol extracts have significant antioxidant, cytotoxic, analgesic, and anti-diarrheal activity. HIGHLIGHTS The extract’s phytochemical analyses found flavonoids, alkaloids, saponins, tannins, glycosides, and carbohydrates The GC-MS analysis of the methanol extract identified 8 compounds. The major components were identified as Diisooctyl phthalate (96.903 %), 2-methyltetracosane (1.094 %) The antioxidant and cytotoxicity studies suggest that methanol extract has a more potent antioxidant and cytotoxic capacity than hexane extract The findings from in-vivo study of the leaves of the reticulatum also exhibited that methanol extracts have significant analgesic, and anti-diarrheal activity GRAPHICAL ABSTRACT